Comprehensively dissecting the hub regulation of PkaC on high‐productivity and pellet macromorphology in citric acid producing Aspergillus niger - Xiaomei Zheng; Timothy C. Cairns; Xiaomei Ni; Lihui Zhang; Huanhuan Zhai; Vera Meyer; Ping Zheng; Jibin Sun (Microbial Biotechnology, 2022)
Summary Aspergillus niger, an important industrial workhorse for citric acid production, is characterized by polar hyphal growth with complex pelleted, clumped or dispersed macromorphologies in submerged culture. Although organic acid titres are dramatically impacted by these growth types, studies that assess productivity and macromorphological changes are limited. Herein, we functionally analysed the role of the protein kinase A (PKA)/cyclic adenosine monophosphate (cAMP) signalling cascade during fermentation by disrupting and conditionally expressing the pkaC gene. pkaC played multiple roles during hyphal, colony and conidiophore growth. By overexpressing pkaC, we could concomitantly modify hyphal growth at the pellet surface and improve citric acid titres up to 1.87‐fold. By quantitatively analysing hundreds of pellets during pilot fermentation experiments, we provide the first comprehensive correlation between A. niger pellet surface morphology and citric acid production. Finally, by intracellular metabolomics analysis and weighted gene coexpression network analysis (WGCNA) following titration of pkaC expression, we unveil the metabolomic and transcriptomic basis underpin hyperproductivity and pellet growth. Taken together, this study confirms pkaC as hub regulator linking submerged macromorphology and citric acid production and provides high‐priority genetic leads for future strain engineering programmes.